WORK ENVIRONMENT INTERACTION AND GENDER USE OF MANAGERIAL SKILLS IN CV NUSANTARA ABADI YOGYAKARTA - Lastari, Siwi (Management, 2010)
With regard to gender, there was no interaction effect between the environment for managerial development and gender on the use of managerial skills, although gender itself affect the managerial skills. In other words gender in environmental CV. Nusantara Abadi has no effect on the working environment, where the working environment has positive influence on the use of managerial skills. Instrumentality-expressiveness views which say that women are more interested in the work environment than men and men tend to be interested in working careers than women did not apply to the working environment in CV. Abadi Nusantara. Both men and women together to create a supportive working environment for managerial development, so that a positive work environment affect the use manajerial.Bila skills associated with a previous study, the research conducted by the Ziguang Chen, Norihiko Takeuchi, & Mitsuru Wakabayashi, there similarities and differences in research results. The equation is proven first hypothesis which states that the environment for managerial development of positive effect on the use of managerial skills. The difference with previous research results of this study are: When this study found no effect of interaction between the environment for managerial development and gender on the use of managerial skills, then the previous studies found no effect of interaction between the environment for managerial development and gender in the use of managerial skills. The study also found that a positive relationship between work environment and use of managerial skills are stronger in women managers. Keyword : Environment, Gender, Managerial